Thermodynamic analysis of CO2 removal process by adsorption on NaX (2021)
The continuous increase of carbon dioxide concentration in the atmosphere is the main contributor to climate change. Thus, it is imperative to develop strategies that help to control manmade emissions of this gas. Carbon dioxide capture is an intensive research area that aims to decrease the energy requirements for the separation and storage of CO2. Even though absorption using an aqueous solvent is a well-established and is the most widely implemented capture technology, it requires high energy for the regeneration of the solvent due to the need to increase the temperature of the aqueous solvent, decreasing the overall efficiency of the process. Adsorption using porous solids has been presented as an alternative process to capture CO2 while decreasing the energy requirements. In the present work, a thermodynamic analysis of the CO2 removal process by adsorption using literature reported data is performed, in order to devise a framework to evaluate and compare two adsorbents under realistic process conditions. Zeolites NaX and Beta were used as case studies to evaluate the proposed model. The results show that, although bed composition profiles have similar trends for both adsorbents, there is a significant difference in the regeneration temperature of these adsorbents, since for zeolite NaX the regeneration temperature is reached around 360K when CO2 is almost pure, whereas for Beta this value is reached around 390K. Thus, NaX has a lower energy requirement than Beta for stablished process conditions. The energy penalty is 91.08 MW per molCO2 recovered for NaX and 104.28 MW per molCO2 recovered for Beta, which is consistent with the calculation of the specific thermal energy and the working capacity.